SAE Technical Paper Series 2015
DOI: 10.4271/2015-01-1190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Vehicle Fast Charging on Battery Life and Vehicle Performance

Abstract: As part of the U.S. Department of Energy's Advanced Vehicle Testing Activity, four new 2012 Nissan Leaf battery electric vehicles were instrumented with data loggers and operated over a fixed onroad test cycle. Each vehicle was operated over the test route, and charged twice daily. Two vehicles were charged exclusively by AC level two electric vehicle supply equipment, while two were exclusively DC fast charged with a 50 kilowatt fast charger. The vehicles were performance tested on a closed test track when ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…An experimental study in Phoenix, Arizona found slightly increased rates of SoH decline in two 24 kWh Leafs that were always rapid charged compared to two others that were slow charged 320 (Shirk, 2015). The sample size was small, the experiment lasted only a year and a half, and the vehicles were driven extraordinarily long distances in much hotter conditions than prevail in New Zealand.…”
mentioning
confidence: 99%
“…An experimental study in Phoenix, Arizona found slightly increased rates of SoH decline in two 24 kWh Leafs that were always rapid charged compared to two others that were slow charged 320 (Shirk, 2015). The sample size was small, the experiment lasted only a year and a half, and the vehicles were driven extraordinarily long distances in much hotter conditions than prevail in New Zealand.…”
mentioning
confidence: 99%
“…A simple exemplary calculation is feasible using this formula. Assuming a typical temperature collectively taken from [20], an operating time (lifetime) of 8000 h, an activation energy for the gap filler of 0.45 eV [21], and a test temperature of 85 • C, then the average acceleration factor is 8.4 which means that the lifetime is reached within 958 h of testing time, as shown in Table 1.…”
Section: Arrhenius Modelmentioning
confidence: 99%
“…Although some specific EV batteries are designed for fast charging, they will in fact degrade slightly faster when charged with DC fast charging. In a comparison of two Nissan Leafs, with one vehicle using only slow charging and the other fast charging, after 50,000 km the type of charging had only a small effect on battery capacity with a maximum amount of 5 percent additional degradation (Shirk and Wishart 2015). -Driving behavior and loading.…”
Section: Battery Performance and Life Spanmentioning
confidence: 99%